Аджидере / Хаджидере: до питання османської назви селища Овідіополь - Середа, О. (Чорноморська минувшина, 2020)
Метою цієї статті є дослідження використання османської назви сучасного селища Овідіополь від першої згадки населеного пункту до остаточного перейменування його російським урядом (1756 – 1794). На прикладах надано позначення населеного пункту в османсько-турецьких джерелах і трансформація назви при перекладах на інші мови і зокрема на російську. Введено у науковий обіг нового джерела – картографічного зображення Дністровського лиману з позначеними ключовими населеними пунктами на його берегах та визначеними сферами судноплавства протоками лиману з Чорним морем. The purpose of this article is to study the use of the Ottoman name of the modern village of Ovidiopol from the first mention of the settlement to its final renaming by the Russian government (1756 - 1794). The examples show the designation of the settlement in Ottoman-Turkish sources and the transformation of the name when translated into other languages and in particular into Russian. One of the first known written mentions of the name of Adzhidere can be found in Ottoman-Turkish sources of the middle of the XVIII century. from the Government Ottoman Archives in Istanbul. In particular, the oldest designation of the settlement on the site of the modern village of Ovidiopol is in an extract from the port log / defter, which contains information on loading and dispatching merchant ships from Adzhidere Pier to Istanbul's harbor Kapan-i Dakik - the coastal quarter in Golden Horn Bay. The annotation to this document states that the port log / defter is the register of loading and dispatch of grain from the port of Adzhidere since the beginning of the month of Muharram in 1170 AH, which corresponds to the date from September 26, 1756. In the report of the Russian intelligence of 1758 Ovidiopol is already mentioned as Gadzhidere. In particular, it is reported about the purchase of wheat and rye by Turks, Crimean Tatars, Nogai, Greeks and Wallachians, and its transportation to “different cities such as Ochakov, Belgorod and Hadzhidere, Bender, Kiliya, Smailov (Izmail) and the Wallachian city Iasi” The next source, with the designation Adzhidere, are the Ottoman-Turkish documents of the Governmental Ottoman Archive in Istanbul from the collection “State Administration”, dated 1765. The documents contain several different texts from public institutions and resolutions to be implemented. A number of sources of the next period of 1780-90s indicate the Ottoman name of modern Ovidiopol both Adzhidere and Hadzhidere. Thus, in the travel description of the French engineer Lafitte-Clave, who worked for the military department of the Ottoman Empire in 1784-87, “Hadzhi Dere” was mentioned. In the description of the Ochakov land made by the Russian engineer De Volan in 1791, it is said about Adzhidere after the Russo-Turkish wars. Such double names of settlements are sometimes found in Ottoman documents due to the ignorance of the Ottoman bureaucracy of toponyms of remote regions of the Ottoman state. Such a document is the Ottoman map of 1790, as evidenced by the content of inscriptions and explanations to the settlements. A new source has been put into scientific circulation - a cartographic image of the Dniester estuary with marked key settlements on its shores and defined areas of navigation through the estuary straits with the Black Sea.